What do Latin Americans expect from democracy? An analysis of variance model (ANOVA) - Miranda Delgado, Rafael Gustavo (2021)
The objective of this research is to analyze the impact of material variables on the satisfaction of democracy in Latin America. The hypothesis that guides this research is that material variables such as security, poverty reduction, equity and employment have a significant impact on the satisfaction of Latin American citizens with their democratic regimes. The research showed that the material variables are significant for understanding citizen satisfaction with democracy. Material variables explain more than 30% of the satisfaction, or dissatisfaction, of democracy in the region. The most demonstrative variables in the satisfaction of democracy are the poverty gap, and then the victimization rate.